Environmental monitoring and risk assessment of organophosphate pesticides in aquatic ecosystems of north-west Bangladesh. (September 2018) - Sumon, Kizar Ahmed; Rashid, Harunur; Peeters, Edwin T.H.M.; Bosma, Roel H.; Van den Brink, Paul J.
Abstract: The use of organophosphate pesticides (OPPs) to protect a variety of crops has increased in Bangladesh. OPPs may contaminate surrounding aquatic environments through several routes including spray drift, surface runoff and groundwater leaching. Since it is unknown how much OPP end ups in aquatic environment in Bangladesh, the objectives of the present study were to quantify the residues of ten most commonly used OPPs in water and sediment of water bodies of north-west Bangladesh and to assess their ecological risks for aquatic organisms. The risks of the pesticides in surface water and sediment were assessed using a first-tier risk quotient (RQ) approach. The higher-tier PERPEST model was used to refine the ecological risks of pesticides when RQ indicated a potential risk. Results showed the most frequently detected pesticides that appeared in high concentrations were chlorpyrifos, diazinon and quinalphos in surface water and sediment. The highest concentration of OPPs measured in water was 9.1 μg chlorpyrifos/L (median of 1.95 μg/L), while this was 51 μg diazinon/kg dw (median of 11 μg/kg dw) for sediment. Furthermore, results showed high acute and/or chronic RQs (RQ > 1) in surface water and sediment for chlorpyrifos, diazinon, quinalphos, malathion and fenitrothion. The higher-tier PERPEST model confirmed risks of chlorpyrifos, diazinon, quinalphos and fenitrothion for aquatic insects, micro- and macro-crustaceans which were previously derived by RQ-based risk assessment for aquatic organisms. Furthermore, the results of the PERPEST model also indicated possible indirect effects of these pesticides on algae and macrophytes, community metabolism, rotifers and other macro-invertebrates. Highlights: Chlorpyrifos, diazinon and quinalphos were more frequent in water and sediment samples. The highest concentration of OPPs in water was measured for chlorpyrifos as 9.1 μg/L. The highest concentration of OPPs in sediment was measured for diazinon as 51 μg/kg. RQs showed higher risks of most OPPs for Daphnia than fish and algae. The higher-tier PERPEST model refined the risks for invertebrates.